Radon exposure and oropharyngeal cancer risk. Issue 1 (1st December 2015) - Salgado-Espinosa, Tania; Barros-Dios, Juan Miguel; Ruano-Ravina, Alberto
Highlights: Radon exposure might be linked with oral and pharyngeal cancers. The available literature does not show an association between radon exposure and these tumours. This association does not appear to exist neither for miners nor for general population. No study has been found analysing directly this association. Such studies are encouraged. Abstract: Oropharyngeal cancer is a multifactorial disease. Alcohol and tobacco are the main risk factors. Radon is a human carcinogen linked to lung cancer risk, but its influence in other cancers is not well known. We aim to assess the effect of radon exposure on the risk of oral and pharyngeal cancer through a systematic review of the scientific literature. This review performs a qualitative analysis of the available studies. 13 cohort studies were included, most of them mortality studies, which analysed the relationship between occupational or residential radon exposure with oropharyngeal cancer mortality or incidence. Most of the included studies found no association between radon exposure and oral and pharyngeal cancer. This lack of effect was observed in miners studies and in general population studies. Further research is necessary to quantify if this association really exists and its magnitude, specially performing studies in general population, preferably living in areas with high radon levels.